Twentieth conference on Interdisciplinary Management Research – Osijek, IMR XX 2024 - Jerko Glavaš; Ivana Unukić (Ekonomski Vjesnik)
IMR 2024: At the heart of the Slavonian Plain, Osijek hosted the twentieth edition of the Interdisciplinary Management Research (IMR conference that took place on 24 and 25 October 2024. This prestigious gathering, which has been bringing together the academic community, researchers, professionals and doctoral students for two decades, was organized in cooperation with the Faculty of Economics and Business in Osijek, Pforzheim University (Germany), and the Faculty of Economics at the University of Bihać. The IMR XX conference confirmed its status as a leading platform for the exchange of ideas and interdisciplinary research achievements on the international scene, inspiring all attendees with its tradition and influence.